The Impact of Local Taxes, Population Growth and Inflation on Islamic Economic Growth Perspectives - Jamaludin, Jamaludin; Hafiduddin, Ahmad Didin; Alfialhubufillah, M; Husenuddin, Abdullah (Li Falah: Journal of Islamic Economics and Business, 2023)
This study aims to understand the impact of local taxes, population growth and inflation on economic growth from an Islamic perspective. The method employed is a quantitative study using secondary data from the Central Statistics Agency (BPS), which is then processed using E-Views 9 software. The technique utilized is panel data regression, combining cross-section data with time series data, and analyzed using the Fixed Effect Model (FEM) estimation model. The results indicate that the local tax variable has a significant positive impact on economic growth from an Islamic viewpoint. Islam encourages taxation as a means of generating revenue for public welfare while emphasizing fair and responsible collection. Meanwhile, the variables of population growth and inflation have a significant negative impact on economic growth from an Islamic lens. Islamic teachings promote a balanced population policy and stable prices to ensure sustainable economic development aligned with Islamic principles of moderation and justice. The findings highlight the importance of considering Islamic economic perspectives when analyzing the influence of key factors on economic growth.